PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL - Wijaya, Silfi Lestari; Lucyanda, Jurica (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2010)
This study empirically examined the relationship between budget participation and managerial performance. Using a purpose sampling method and regression analysis the result indicate that relationship between budget participation and managerial performance significant effect and positive. The finding support the previous researchsin this area (Brownell, 1982; Brownell dan Mclnnes,1986; Lucyanda dan Wahyudi, 2006)